Investigating Heavy Metal Contamination in Groundwater of Agricultural Areas: The Case Study of Shekhan, Duhok, Iraq - Mohammed, Rangeen Shihab; Nazif, Hindreen Mohammed; Kareem, Idrees Majeed; Ahmed, Ahmed Mohamed (Engineering, Technology & Applied Science Research, 2024)
This study assesses water quality and heavy metal concentrations in 17 main groundwater sources in Duhok City, Iraq’s agriculturally vital Shekhan area. It is important to comprehend the possible health concerns associated with heavy metal pollution in this area because of its relevance to food production. With an emphasis placed on heavy metal concentrations in groundwater sources to support public health and sustainable practices, this study provides essential insights into controlling water quality for irrigation and safe consumption. The Water Quality Index (WQI) results ranged from 15.23 to 37.05, indicating good and excellent water quality, well-suited for drinking and agricultural purposes. The results of heavy metals concentration from Copper (Cu), Manganese (Mn), Lead (Pb), and Nickel (Ni) ranged from 0.0002 to 0.0111 ppm, 0.0023 to 0.0187 ppm, 0.0006 to 0.0024 ppm, and 0.007 to 0.032 ppm, respectively. The World Health Organization (WHO) criteria were satisfied by all heavy metal concentrations in the water samples, except Cadmium (Cd), which exceeded the recommended threshold in six analyzed sources and varied from 0.0015 to 0.0158 ppm. The water is appropriate for irrigation and consumption, according to the findings of the heavy metal content analysis and water quality evaluation, while continuous monitoring is needed to guarantee optimum water quality.